Pengaruh Live Streaming dan Review Product Terhadap Keputusan Pembelian di Marketplace - Putri Watini; Halimah Zahrah (Indo Publishing, 2026)
The development of information technology has driven a shift in consumer shopping behavior from offline to online, particularly through e-commerce platforms like Shopee. One widely used digital marketing strategy is live streaming and the use of product reviews as a source of information and consumer trust. This study aims to analyze the influence of live streaming and product reviews on purchasing decisions for Freaky Official Shop products on Shopee. This study used a quantitative approach with a survey method. The study population was 4,396 Freaky Official Shop consumers in Bandung City in December 2025, with a sample of 368 respondents determined using the Slovin formula and purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS version 27. The results showed that live streaming partially had a positive and significant effect on purchasing decisions, while product reviews also had a positive and significant and dominant effect. Simultaneously, live streaming and product reviews significantly influenced purchasing decisions. The results of this study indicate that a marketing strategy through live streaming and effective product review management can improve consumer purchasing decisions on e-commerce platforms